O členkih, zlasti o njihovih razločevalnih lastnostih - Krvina, Domen (Jezik in slovstvo, 2018)
Particles, as opposed to adverbs (objective expression of circumstances), always reflect the subjective evaluation of the speaker/author of the text; therefore, their meaning - as far as the accuracy and completeness of lexicographic description is concerned - is somewhat difficult to capture fully. For a transition from adverbs to particles to take place, a subjective approach to assessment/evaluation is a necessary prerequisite. This transition is characteristic of de-adjectival adverbs designating a relative property or evaluation. Compared to interjections (modifiers of the entire sentence), particles are inevitably grammatically-semantically bound to individual sentence elements, functioning as modifiers within the sentence. The content of both particles and interjections is a speech act rendering them the role of function words, which in turn means they are best described by so-called functional dictionary definitions. In interjections, their primary meaning of general mood expression can, through predicative responsiveness, be converted and narrowed into a particle one, quite commonly expressing negative attitude. In words that are solely particles, the dictionary entry frequently reflects the swapping of the prevailing modality role (expressing the speaker's attitude towards the reported text) with a text-connecting role. In the majority of cases, the relationship between the use of a particular word as a conjunction and as a particle calls for an independent dictionary description of two (linked) homonyms, with the prevailing modality having its own particle entry.
Keywords: členek; členki; členkovna raba; leksikografija; prislovi; slovarske razlage; slovenščina